Migrations in times of economic crisis: Reflections on labour, inequality and imprisonment in Italy - Crocitti, Stefania (European journal of criminology, 2022)
The Great Recession (2008-13) produced several changes in migratory flows and stock, return migration and foreigners’ legal status, employment, involvement in crime and punishment. In the international context, Italy showed some peculiarities. Unlike other South European countries, Italy did not experience a great worsening of the working conditions of immigrants. Moving from the political economy of punishment approaches (in both traditional and recent declinations), the article describes variations in migration during the recession in Italy, and particularly in immigrants’ working conditions, in order to discuss whether and how punitivity against foreigners (measured by incarceration) has been affected by changes in migrants’ inclusion within Italian society and labour market. The decline in foreigners’ imprisonment is explained by social and economic forces pertaining not to the whole Italian social structure but to a subsystem reserved for migrants that I call ‘migrant social structure’.